Polymeter fibers and natural fibers for vehicular pavement structures in Perú - Palomino Quispe, Justiniano Félix; Choque Flores, Leopoldo; Requis Carbajal, Luis Villar; Castro León, Alisson Lizbeth (European Public & Social Innovation Review, 2024)
Introduction: Polymeter fibers and natural fibers for vehicular pavement structures in Peru. The objective of this systematic review was to analyze technical information on polymer fibers and natural fibers for vehicular pavement structures in Peru. The applied methodology had a qualitative bibliographic approach, whose design was framed in the literature review and documentary analysis of fifty scientific productions, published in journals indexed to the databases: Scopus, and scielo. The main results indicate that natural fibers and polymer are a good option for reinforcing flexible pavements, since good results were obtained in the tests carried out.